1997
DOI: 10.1103/physrevb.56.12529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface impurities on surface diffusion of CO on Ni(110)

Abstract: A small amount of coadsorbed impurity species could significantly alter the surface diffusion of CO on Ni͑110͒. Three impurity species, sulfur, oxygen, and potassium are studied here. The former two are known as ''poisons'' and the latter as a ''promoter'' for CO hydrogenation on Ni. All three are found to impede CO diffusion drastically. The apparent diffusion activation energy E D increases from the clean-surface value of 2-3 kcal/mol, to a saturation value of 7-8 kcal/mol at sufficiently high impurity cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Certainly a direct comparison between these systems is not, in any way, justified. This conclusion is supported by the most recent linear optical diffraction results which have shown that the diffusion of CO along both the ͓110͔ and ͓001͔ directions on Ni͑110͒ have almost the same barrier of ϳ100 meV, 9 contrasting strongly with the factor 2 anisotropy calculated for CO/Pt͑110͒. ͑5͒ A more meaningful comparison for the Ge and King calculations is with the CO/Pt͑111͒ system for which QHAS results were reported early in 1998, 13 and which are not cited in their work.…”
supporting
confidence: 76%
“…Certainly a direct comparison between these systems is not, in any way, justified. This conclusion is supported by the most recent linear optical diffraction results which have shown that the diffusion of CO along both the ͓110͔ and ͓001͔ directions on Ni͑110͒ have almost the same barrier of ϳ100 meV, 9 contrasting strongly with the factor 2 anisotropy calculated for CO/Pt͑110͒. ͑5͒ A more meaningful comparison for the Ge and King calculations is with the CO/Pt͑111͒ system for which QHAS results were reported early in 1998, 13 and which are not cited in their work.…”
supporting
confidence: 76%
“…[51][52][53][54] We note that surface mobility of hydrogen can decrease by a factor of ϳ60 as the surface carbon coverage was increased from C =0 to C = 0.42 ML at T = 300 K. 52 However, in our case, the amount of impurities was below the AES sensitivity. Comparing our measured diffusion coefficient D with the extrapolated value from QHAS results, we see a difference of more than four orders of magnitude (see Fig.…”
Section: Comparison With Previous Resultsmentioning
confidence: 55%
“…There is some experimental evidence of this kind of interaction for the system Au/KCl(100) [131] but to my knowledge, it has never been incorporated in growth models. Chemical impurities adsorbed on the substrate can change the growth in conventional vacuum, and these effects are extremely difficult to understand and control [132]. Of course, many other possible processes have not been addressed in this review, such as the influence of strain, of extended defects as steps or vacancy islands .…”
Section: Other Growth Situationsmentioning
confidence: 99%